Technologies for Sustainable Global Higher Education - Sousa, Maria José; Machado, Andreia de Bem; Dandolin, Gertrudes Aparecida (Advances in Computational Collective Intelligence, 2024)
Digital technologies are influencing the way we learn, live, work and be in different contexts of society, which has entered a digital age. There are a variety of learning systems that support innovative digital approaches, and universities and organizations around the world are investing in building their own e-learning platforms. Digital technologies are enabling wider access to education and new markets for student recruitment, resulting in increased income prospects for global higher education institutions. Technology enables numerous data and information sources, which give greater access to information and data. It also enables highly virtual environments, which impact teaching and the classroom. The widespread use and application of digital technologies in the teaching and learning process provoke pedagogical inquiry and mediation. It is in this context that Technologies for Sustainable Global Higher Education focuses on analyzing the application of digital technologies in the teaching-learning process. The chapters in this edited collection seek to answer such questions relevant to the context of higher education as: What is the concept of digital technologies? How to use digital technology to mediate the learning process? What technologies are used to qualify education in higher education? The book provides answers to these questions by focusing on issues central to improving education through digital technologies, digital learning, and pedagogical practices in digital education. The book also provides case studies of higher education institutions.